2018
DOI: 10.1007/s13197-018-3104-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation on tropomyosin allergen, proximate composition and mineral elements in giant freshwater prawn (Macrobrachium rosenbergii)

Abstract: Effects of food irradiation on allergen and nutritional composition of giant freshwater prawn are not well documented. Thus, this study aimed to investigate the effects of gamma irradiation on tropomyosin allergen, proximate composition, and mineral elements in . In this study, prawn was peeled, cut into small pieces, vacuum packaged and gamma irradiated at 0, 5, 7, 10 and 15 kGy with a dose rate of 0.5 kGy/h using cobalt-60 as the source, subsequently determined the level of tropomyosin, proximate composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The most surprising result of the present work is that after 193 days from X‐ray treatment no significant differences in the acini diameters were recorded between irradiated and control crayfish, and the histology confirmed a recovered spermatogenesis and lack of signs of cellular degeneration. After 1 month from irradiation at the same dose extensive gonadal damage was described 15 and our results demonstrate that less than 193 days are sufficient to repair the irradiation damage or, at least, that the surviving staminal spermatogonia were able to restart a functional spermatogenesis. The possibility of compensating and recovering a few surviving cells has been demonstrated within the pancrustaceans on larvae of Drosophila melanogaster irradiated with 35 Gy.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The most surprising result of the present work is that after 193 days from X‐ray treatment no significant differences in the acini diameters were recorded between irradiated and control crayfish, and the histology confirmed a recovered spermatogenesis and lack of signs of cellular degeneration. After 1 month from irradiation at the same dose extensive gonadal damage was described 15 and our results demonstrate that less than 193 days are sufficient to repair the irradiation damage or, at least, that the surviving staminal spermatogonia were able to restart a functional spermatogenesis. The possibility of compensating and recovering a few surviving cells has been demonstrated within the pancrustaceans on larvae of Drosophila melanogaster irradiated with 35 Gy.…”
Section: Discussionmentioning
confidence: 51%
“…The dose needed for sterilization in arthropods can reach 300 Gy in the case of Lepidoptera 11 . Sterilization by radiation is already used in some commercial crustaceans, such as Penaeus japonicus , 12 Palaemonetes pugio , 13 and Macrobrachium rosenbergii , 14 with X‐ray doses ranging from 10 12 to 640 Gy 15 …”
Section: Introductionmentioning
confidence: 99%
“…Figure 3d shows the conformational and line alterations of seafood antigenic epitopes caused by γ-irradiation. Recently, Muanghorn et al (2018) found that γ-irradiation caused the loss of protein band density in immunoblot analysis (with polyclonal anti-TM produced in rabbit) of TM in giant freshwater prawn (Macrobrachium rosenbergii) with doses of 10 and 15 kGy at a dose rate of 0.5 kGy/h. Specifically, γ-irradiation changed epitopes structure in allergens, causing the unrecognition by IgG.…”
Section: Gamma or Electron Beam (Eb) Irradiationmentioning
confidence: 99%
“…13 However, non-thermal processing could improve nutrition properties and reduce food immunoreactivity. 14,15 In particular, food irradiation, as a mature and effective food processing technology, treats foods that are safe for humans and do not cause nutritional problems below 10 kGy. 16,17 The FAO and WHO declared that the maximum absorbed dose provided to food should not exceed 10 kGy, unless it is for a legitimate technical purpose.…”
Section: Introductionmentioning
confidence: 99%